Extensive seed and pollen dispersal and assortative mating in the rain forest tree Entandrophragma cylindricum (Meliaceae) inferred from indirect and direct analyses - Monthe, F.K.; Hardy, Olivier J.; Doucet, J.L.; Loo, J.; Duminil, J. (Wiley, 2017)
Pollen and seed dispersal are key processes affecting the demographic and evolutionary dynamics of plant species and are also important considerations for the sustainable management of timber trees. Through direct and indirect genetic analyses, we studied the mating system and the extent of pollen and seed dispersal in an economically important timber species, Entandrophragma cylindricum (Meliaceae). We genotyped adult trees, seeds and saplings from a 400‐ha study plot in a natural forest from East Cameroon using eight nuclear microsatellite markers. The species is mainly outcrossed (t = 0.92), but seeds from the same fruit are often pollinated by the same father (correlated paternity, rp = 0.77). An average of 4.76 effective pollen donors (Nep) per seed tree contributes to the pollination. Seed dispersal was as extensive as pollen dispersal, with a mean dispersal distance in the study plot approaching 600 m, and immigration rates from outside the plot to the central part of the plot reaching 40% for both pollen and seeds. Extensive pollen‐ and seed‐mediated gene flow is further supported by the weak, fine‐scale spatial genetic structure (Sp statistic = 0.0058), corresponding to historical gene dispersal distances (σg) reaching approximately 1,500 m. Using an original approach, we showed that the relatedness between mating individuals (Fij = 0.06) was higher than expected by chance, given the extent of pollen dispersal distances (expected Fij = 0.02 according to simulations). This remarkable pattern of assortative mating could be a phenomenon of potentially consequential evolutionary and management significance that deserves to be studied in other plant populations.